2018
DOI: 10.4081/reumatismo.2018.1027
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to extractable nuclear antigens (ENAS) in systemic lupus erythematosus patients: correlations with clinical manifestations and disease activity

Abstract: The aim was to explore possible correlations of antibodies to extractable nuclear antigens (ENA) with clinical manifestations and disease activity indices in systemic lupus erythematosus (SLE) patients. A total of 70 consecutive SLE patients (64 females) were included. Disease activity was assessed by SLE activity index (SLEDAI), and British Isles Lupus Assessment Group (BILAG). Anti-Ro/SSA correlated positively with, headache (r=0.24, p=0.04), blurring of vision (r=0.25, p=0.03) and SLEDAI (r=0.25, p=0.04) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…33 Meanwhile, an Egyptian study found a much lower frequency of the U1-RNP antibodies (10%). 11 In our study, considering the correlation between autoantibodies and tissue involvement, we found that the anti-dsDNA antibodies have a significant association with mucocutaneous (malar rash, photosensitivity, oral ulcer, alopecia), renal and hematological manifestations. A study by Jurencak et al found that LN and malar rash with anti-dsDNA have a significant association.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…33 Meanwhile, an Egyptian study found a much lower frequency of the U1-RNP antibodies (10%). 11 In our study, considering the correlation between autoantibodies and tissue involvement, we found that the anti-dsDNA antibodies have a significant association with mucocutaneous (malar rash, photosensitivity, oral ulcer, alopecia), renal and hematological manifestations. A study by Jurencak et al found that LN and malar rash with anti-dsDNA have a significant association.…”
Section: Discussionsupporting
confidence: 47%
“…46 It was also significantly associated with consumed C3 (p=0.020), proteinuria (p=0.039), and LAC (p<0.001). Emad et al found a significant correlation with C3 (p value = 0.004), 11 while Hiraki et al correlated them to LAC antibodies. 25 In the opposite of our study, Kini et al observed that the different anti-ENA antibodies and the characteristic organ involvement did not have any association.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations